The subject ‘music’ from inside versus outside the music teaching profession: a comparative case study on the views of music and non-music primary education teachers in Spain. - Mateos-Moreno, Daniel; Bravo Fuentes, Paloma (Routledge / Taylor & Francis, 2023)
Music as a subject in compulsory education is thought to have both a low reputation and a globally declining relevance. However, research findings have been contradictory in exploring the beliefs of teachers on the subject and have mainly targeted the Anglo-Saxon context. With the present study, we aim to shed light on how teachers understand this subject by adopting an approach that is novel to the extant research. By means of a comparative multi-case study, we contrasted the views of purposefully selected music and non-music teachers in the context of primary education in Spain. Our findings indicate that both cases shared a relativistic perspective on the subject's value, which is conceived as highly dependent on the advocacy and in-class teaching methodology adopted by each music teacher, as well as concerns about its teaching methodology. However, our analysis also reveals several discrepancies between the beliefs of both cases that may lead to mutual misunderstandings. Furthermore, our study suggests a lack of understanding of the role and needs of the music teacher by their counterparts, alongside music teachers having false assumptions about their counterparts’ views on their subject. Finally, we provide implications for increasing the perceived relevance of the subject that may also contribute to a better school climate for music teachers in the context of our participants.
Keywords: Música - Estudio y enseñanza; Profesores de música; Music; Teacher; Curriculum; Comparative; Multi-case